S = k = 8 ∑ 3 5 k ( k − 1 ) ( k − 2 ) ( k − 3 ) ( k − 4 ) ( k − 5 ) ( k − 6 )
Given that the sum above can be expressed as a ! × ( j ! b × c × d × e × f × g × h × i − 1 )
where a , b , c , d , e , f , g , h , i are all positive integers with j is the cube of a prime number and b , c , d , e , f , g , h , i are consecutive integers.
Find a + b + c + d + e + f + g + h + i + j .
Bonus
: Generalize the sum,
m
∑
n
(
k
)
(
k
−
1
)
(
k
−
2
)
⋯
(
k
−
(
r
−
1
)
)
such that
m
>
r
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is simply a telescoping series ! . Multiply and divide by 8 and write 8 in the numerator as (k+1)- (k-7) . its done!
Problem Loading...
Note Loading...
Set Loading...
S = m ∑ n ( k ) ( k − 1 ) ( k − 2 ) . . . . . . ( k − ( r − 1 ) )
Multiplying and dividing by r ! ( k − r ) !
S = r ! × m ∑ n r ! × ( k − r ) ! k !
S = r ! × m ∑ n ( r k )
S = r ! × ( r ∑ n ( r k ) − r ∑ m − 1 ( r k ) )
Using the Hockey stick identity ,
r ∑ n ( r k ) = ( r + 1 n + 1 )
∴ S = r ! × ( ( r + 1 n + 1 ) − ( r + 1 m ) )
For the given sum,
n = 3 5 , m = 8 , r = 7
∴ S = 7 ! × ( ( 7 + 1 3 5 + 1 ) − ( 7 + 1 8 ) )
∴ S = 7 ! × ( ( 8 3 6 ) − ( 8 8 ) )
∴ S = 7 ! × ( 8 ! 2 9 × 3 0 × 3 1 × 3 2 × 3 3 × 3 4 × 3 5 × 3 6 − 1 )
Comparing,
a = 7 , b = 2 9 , c = 3 0 , d = 3 1 , e = 3 2 , f = 3 3 , g = 3 4 , h = 3 5 , i = 3 6 , j = 8
∴ a + b + c + d + e + f + g + h + i + j = 7 + 2 9 + 3 0 + 3 1 + 3 2 + 3 3 + 3 4 + 3 5 + 3 6 + 8 = 2 7 5